Life successes for kids! strategies for conquering the childhood obesity epidemic - Krech, Donna; International Health, Racquet and Sportsclub Association; Monterey Bay Video Production Company (Monterey, CA : Monterey Bay Video Production Company, 2007)
Provides an overview of how health/fitness clubs can help reverse the childhood obesity epidemic. Also discusses how to engage children and details the eight basic keys to shaping healthy, happy, succesful young adults
Title from title screen
Keywords: Obesity in children; Overweight children